If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -1x + 36 = 56 Reorder the terms: 24 + 36 + -1x = 56 Combine like terms: 24 + 36 = 60 60 + -1x = 56 Solving 60 + -1x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -1x = 56 + -60 Combine like terms: 60 + -60 = 0 0 + -1x = 56 + -60 -1x = 56 + -60 Combine like terms: 56 + -60 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 2x-10=-10 | | x+4x+7x=91 | | -1+3x=35 | | 6x-108=6 | | x+7x-8=0 | | -4x-2=46 | | 6x-6=-6 | | 6x-7x-4=0 | | -6+7=73 | | -6-5x=14 | | 7(r+3)+2(r-2)= | | 5.2x+3500=6.6x | | 242=.5(4x)(x) | | 2x+17=5x+3 | | 3x^2-30x=4x^2-3x-18 | | -3x+4=-29 | | -3x-12x+2=0 | | 103-7x=11x+15 | | 5t+6=2 | | 5x^2+4x-11=31-25x | | 3x+10=-11 | | 4x+5x-1=0 | | -64-10x=7x+21 | | 6x+8=-58 | | 12x^2+3x-10=4(x-1) | | -26-3X=7X+34 | | 7x^2+3x-11=45-38x | | 972=3x^2 | | 10-4x=30 | | 972=3x^3 | | 2.2y=44 | | 9x+(-17)=55 |